Indoor environmental quality (IEQ) acceptance of air conditioned buildings in Malaysia: Case study of Universiti Tenaga Nasional - Asadi I.; Hussein I.; Palanisamy K. (Trans Tech Publications Ltd, 2023)
Indoor environmental quality (IEQ) is an important topic which impacts on energy efficiency and also productivity of occupants. Thermal comfort, indoor air quality, visual comfort and aural comfort are four main physical parameters which are normally used to determine IEQ. In this paper, the results of field study on IEQ conducted in the offices and student study areas of 6 air conditioned buildings in Universiti Tenaga Nasional in Malaysia are presented. The study was conducted during the month of October and November 2013, collecting a full set of objective physical measurements and subjective assessments through questionnaires. The measured environmental parameters are indoor air temperature, relative humidity, air velocity, carbon dioxide concentration, sound pressure level and luminance. The subjective responses concern the judgment of the respondents about the IEQ parameters at the moment of measurements. The results obtained showed that 86% of the respondents found that the IEQ is acceptable and the environmental conditions are mainly within the limits set by the various guidelines and standards in Malaysia. The neutral IEQ values were also determined through linear regression analysis of the sensation votes. © (2014) Trans Tech Publications, Switzerland.